Identifying and Monitoring Water Quality Needs for Puget Sound’s Aquaculture Industry and Environmental Security Through the Design and Use of a Prototype Sensor Suite - Hammermeister, Emily (My University, 2019)
The impact of climate change on the environmental and economic security of marine resources has now entered the public and political discourse. The sectors of the marine industry that must make both short and long-term operational decisions under conditions of uncertainty regarding both the magnitude of ecological change and the response in governing policies, seek sources of trusted information which can guide their investments. The shellfish industry is a significant sector of the seafood industry, especially in the Puget Sound region of Washington State. This research identifies the water quality monitor needs of shellfish farmers and designs a prototype sensor suite at a favorable price point to provide both operational and long-term data for investments in light of uncertain localized climate change impacts.
Keywords: Shellfish; Water quality; Puget Sound; Aquaculture; Prototype sensor